1991
DOI: 10.1152/jappl.1991.70.2.701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mean airway pressure on gas exchange during high-frequency oscillatory ventilation

Abstract: We studied the effect of mean airway pressure (Paw) on gas exchange during high-frequency oscillatory ventilation in 14 adult rabbits before and after pulmonary saline lavage. Sinusoidal volume changes were delivered through a tracheostomy at 16 Hz, a tidal volume of 1 or 2 ml/kg, and inspired O2 fraction of 0.5. Arterial PO2 and PCO2 (PaO2, PaCO2), lung volume change, and venous admixture were measured at Paw from 5 to 25 cmH2O after either deflation from total lung capacity or inflation from relaxation volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Kolton et al (12) and Lachmann et al (15) demonstrated that FRC decreases after lavage. We have previously shown that increasing lung volume in lavaged rabbits decreases venous admixture and improves oxygenation (14). Healthy and lavaged rabbits may not have differed with respect to effects of Haw because 5 cm H20, the lowest value studied, may have exceeded closing pressure for the lavaged animals, or because the inflation maneuver between changes of settings may have transiently eliminated differences in lung volume.…”
Section: Frequency (Hz)mentioning
confidence: 93%
See 2 more Smart Citations
“…Kolton et al (12) and Lachmann et al (15) demonstrated that FRC decreases after lavage. We have previously shown that increasing lung volume in lavaged rabbits decreases venous admixture and improves oxygenation (14). Healthy and lavaged rabbits may not have differed with respect to effects of Haw because 5 cm H20, the lowest value studied, may have exceeded closing pressure for the lavaged animals, or because the inflation maneuver between changes of settings may have transiently eliminated differences in lung volume.…”
Section: Frequency (Hz)mentioning
confidence: 93%
“…Our resgts suggest that the combined effect of a V, of 2 mL/kg and a Pa, greater than or equal to 10 cm H 2 0 arc necessary to produce adequate oxygenation. We assume that Pa, improved oxygenation by increasing lung volume and decreasing venous admixture (14). The suboptimal oxygenation that occurs at lower frequencies for a V, of 1 mL/kg and Pa, of 5 cm H 2 0 (Figs.…”
Section: Frequency (Hz)mentioning
confidence: 99%
See 1 more Smart Citation
“…From a physiological standpoint it is unlikely that the control of ventilation and oxygenation are truly independent from each other during HFOV [11][12][13]. Changes in functional residual capacity (FRC) during a recruitment procedure will almost certainly impact on lung compliance and oscillation volume (Vosc), as the position of ventilation changes along the inflation and deflation limbs of the pressure-volume curve [12][13][14][15].…”
mentioning
confidence: 99%
“…22,[53][54][55][56][57][58][59] By doing so, less CDP is needed to maintain a certain lung volume on the inflation limb, because of the hysteresis of the respiratory system. In our view and practice, this can be achieved in clinical practice in patients with DAD by initially setting the CDP 3-5 cm H 2 O above the mean airway pressure on conventional mechanical ventilation, as the distal CDP is lower than the set proximal CDP.…”
Section: Best Hfov Approach and Oscillator Settings For Oxygenationmentioning
confidence: 99%